Relationship between tinnitus pitch and edge of hearing loss in individuals with a narrow tinnitus bandwidth - Sereda, Magdalena; Edmondson-Jones, Mark; Hall, Deborah A. (Taylor & Francis, 2015)
Objective: Psychoacoustic measures of tinnitus, in particular dominant tinnitus pitch and its relationship to the shape of the audiogram, are important in determining and verifying pathophysiological mechanisms of the condition. Our previous study postulated that this relationship might vary between different groups of people with tinnitus. For a small subset of participants with narrow tinnitus bandwidth, pitch was associated with the audiometric edge, consistent with the tonotopic reorganization theory. The current study objective was to establish this relationship in an independent sample. Design: This was a retrospective design using data from five studies conducted between 2008 and 2013.